Anal Fissure: A Strong Treatment 15 Years of Evidence - Sánchez, Morelos Adolfo García; González, Mireya De La Fuente; Rodríguez, María Isabel Estrada; Bonola, Yamileth Jiménez; General, Mauricio Israel Flores Pazos; Vargas, Astrid Ortiz (British Journal of Healthcare and Medical Research, 2022)
Anal fissure is a very common disease and is defined as a linear tear or injury or ulcer, involving the anoderm perpendicular to the pectineal area at the edge of the anus. Anal fissure is classified as acute, less than 6 weeks duration of symptoms and chronic with a time greater than this. The objective is to describe the experience of the results obtained from the surgical treatment of chronic anal fissure in four different hospitals, second and third level care. Material and methods: it is described as a study with a retrospective, longitudinal, observational and descriptive design, with the presentation of the results carried out through descriptive biostatistical procedures. The results were 2,728 surgical procedures of fistulectomy with open lateral internal sphincterotomy, which were 1,853 women (68%) and 875 men (32%). With an age range of 17 to 81 years. No recurrence or surgical reintervention was documented, no patient readmission was reported 30 days after surgery, and there was no mortality. Discussion: the treatment of chronic anal fissure is multiple and varied, in the first place general management measures should be initiated, the use of multiple topics, chemical sphincterotomy, as well as surgical management with many of its variants. In conclusion, fissurectomy with open lateral internal sphincterotomy with a 33% cut of the internal anal sphincter achieves a high rate of success in healing, zero complications and no recurrence, with level II scientific evidence in regard to international medical literature.